Microencapsulation of bacterial strains in graphene oxide nano-sheets using vortex fluidics - Wahid, M.; Eroglu, Ela; LaVars, S.; Newton, K.; Gibson, C.; Stroeher, U.; Chen, X.; Boulos, R.; Raston, C.; Harmer, S. (2015)
© The Royal Society of Chemistry 2015. Wrapping bacterial cells with graphene oxide sheets using a vortex fluidic device (VFD) effectively limits cellular growth for a certain time period whilst sustaining biological activity. This simple and benign method in preparing such a composite material relies on the shear within the film in the device without compromising the cellular viability. In principle, the process is scalable for large volumes, for operating the VFD(s) under continuous flow mode. Moreover, acquiring SEM images was possible without pre-coating the composite material with a metallic film, with limited charging effects. This establishes the potential for interfacing material with graphene oxide, which could be extended to more conductive graphene layers, as an effective approach for simplifying characterization using SEM.